Structural analysis and design of a long span combined cable-stayed suspension bridge crossing the Izmit Bay - Zengin, Esra. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
In designing long span cable supported bridges, geometrical nonlinearity of the structure, including the cable sags, large deflections, and P-Delta effects, is a primary consideration. Also, reaching the initial equilibrium configuration of a cable supported bridge, via a set of geometrically-nonlinear analyses under dead loads, is essential in obtaining the stiffness properties of the cable elements for further analyses. In order to determine the static and dynamic behaviour of the cable supported bridges accurately, static and dynamic analyses should be conducted by considering all sources of geometric nonlinearity. In this thesis, a particular analytical model has been developed for a proposed longspan combined cable-stayed suspension bridge crossing the Izmit Bay. To evaluate the behavior and response of the cable supported bridge, a series of static and dynamic analyses have been conducted under code-compliant service loads as well as using extreme load effects. Bridge displacements and internal forces in the structural members as a result of the applied forces and earthquake effects were calculated in accordance with the load combinations specified by AASHTO-LRFD (2007). Member capacities and deformations were checked per the ASSHTO-LRFD specifications and the structural performance of the proposed bridge was evaluated. The Bosphorus suspension Bridge in Istanbul was also modeled and analyzed within the scope of this work, as a preliminary case study to assess the validity of the modeling and analysis methodologies used.
Keywords: Cable-stayed bridges.